2017
DOI: 10.1186/s12891-017-1621-2
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial inhibitor oligomycin induces an inflammatory response in the rat knee joint

Abstract: BackgroundRecent findings support a connection between mitochondrial dysfunction and activation of inflammatory pathways in articular cells. This study investigates in vivo in an acute model whether intra-articular administration of oligomycin, an inhibitor of mitochondrial function, induces an oxidative and inflammatory response in rat knee joints.MethodsOligomycin was injected into the rat left knee joint on days 0, 2, and 5 before joint tissues were obtained on day 6. The right knee joint served as control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Likewise, we observed that animals under H 2 S treatment showed an upregulated expression of Nrf-2, NQO1 and HO-1, suggesting that the activation of this signaling pathway could be involved in the antioxidant effect of H 2 S. These findings are in accordance with the fact that the downregulation of Nrf-2/HO-1 signaling increases OA severity, whereas its induction elicits protective actions in this pathology [ 59 , 60 ]. Nonetheless, we and other authors observed an upregulation of Nrf-2 levels in OA joint, likely as an insufficient response against the oxidative stress generated during this articular disorder [ 61 , 62 ]. Additionally, a recent study described that the expression of Nrf-2-regulated detoxicant enzymes, such as HO-1 and NQO1, is significantly increased in MIA-injected mice and that treatment with slow H 2 S-release donors maintains these high levels [ 27 ].…”
Section: Discussionmentioning
confidence: 48%
“…Likewise, we observed that animals under H 2 S treatment showed an upregulated expression of Nrf-2, NQO1 and HO-1, suggesting that the activation of this signaling pathway could be involved in the antioxidant effect of H 2 S. These findings are in accordance with the fact that the downregulation of Nrf-2/HO-1 signaling increases OA severity, whereas its induction elicits protective actions in this pathology [ 59 , 60 ]. Nonetheless, we and other authors observed an upregulation of Nrf-2 levels in OA joint, likely as an insufficient response against the oxidative stress generated during this articular disorder [ 61 , 62 ]. Additionally, a recent study described that the expression of Nrf-2-regulated detoxicant enzymes, such as HO-1 and NQO1, is significantly increased in MIA-injected mice and that treatment with slow H 2 S-release donors maintains these high levels [ 27 ].…”
Section: Discussionmentioning
confidence: 48%
“…We selected oligomycin to reprogram monocytes in this study over other metabolic inhibitors because it is less potent and would dampen but not completely block OxPhos, whereas stronger inhibitors, such as rotenone, are extremely toxic and have been shown to inhibit MF viability and function [51][52][53][54]. In addition, a nanoparticle-directed method was preferred for in vivo administration because of potential toxicity associated with a non-targeted systemic delivery approach [55,56]. In this study, nanoparticles were conjugated with tuftsin to facilitate FcR-mediated uptake in monocytes [36], which are the most abundant mononuclear phagocyte population during S. aureus PJI [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we asked whether mitochondrial dysfunction could result in the activation of PKR, which can disrupt cell homeostasis by suppressing translation and initiating apoptotic programs. To trigger mitochondrial dysfunction, we treated SW1353 chondrosarcoma cells with oligomycin A (oligoA) to inhibit ATP synthase of the mitochondrial respiratory chain complexes (MRCs), as described in previous studies 44,45 . Using JC-1 dye, we confirmed that oligoA treatment damages mitochondria, which is reflected in the disruption of mitochondrial membrane potential ( Fig.…”
Section: Inhibition Of Mitochondrial Respiratory Chain Activates Pkrmentioning
confidence: 99%